Дослідження кінетичних характеристик зразків твердої біомаси - Schudlo T.S.; Dunaevskaya N.I. (General Energy Institute of the National Academy of Sciences of Ukraine, 2016)
The article is devoted to the issue of improving the environmental performance of TPP of Ukraine by introducing them to pulverized coal and solid biomass co-firing technology. The samples of wood and wheat straw, corn, rape and soybeans were investigated by means of thermogravimetry. Determined individual stage of solid biomass thermal conversion and obtained kinetic constants for dehydration and devolatilization stages. The data and its comparison with the research of other authors point to possible significant differences in the characteristics of the solid biomass of individual species and different samples of the same species.